Molecules and targets of antidiabetic interest - Kavishankar Gawli; Kavya Sritha Bojja (Elsevier, 2024)
Background: The review is a comprehensive overview of targets of antidiabetic interest and molecules that are reported to possess modulatory effects on glucose homeostasis. Drugs available in the market to treat diabetes restore blood glucose levels to normal, but are associated with undesirable effects. This has compelled the investigators to search for a more benign candidate molecule that could counter the high levels of blood glucose, minimize, or diminish further complications and improve lifestyle. Methods: A literature survey was performed using the scientific databases viz., PubMed, Scopus, Google scholar and EMBASE. Results: Twenty targets and 233 molecules, their source, structure, chemical formula, IC50 values and mechanism of action are described. The review has focused on the growing interest in discovering novel targets such as antagonists of glucagon and glucocorticoids receptor, inhibitors of aldose reductase, fructose-1,6-bisphosphatase, and glycogen phosphorylase that have led to effective clinical development. The enzyme inhibitors, antagonists, agonists, and blockers of receptors are reported to be plant-derived metabolites and therefore, can target cellular and molecular mechanisms leading to glucose homeostasis. Conclusions: Overall, the information could serve as a guide for investigators and drug-based companies to explore the molecules for developing potential antidiabetic drug candidates with fewer or no side effects.